Utilization of a standardized tracheostomy capping and decannulation protocol to improve patient safety. (4th April 2014) - Pandian, Vinciya; Miller, Christina R.; Schiavi, Adam J.; Yarmus, Lonny; Contractor, Anisha; Haut, Elliott R.; Feller‐Kopman, David J.; Mirski, Marek A.; Morad, Athir H.; Carey, John P.; Hillel, Alexander T.; Maragos, Carol S.; et al.
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis To develop and assess the feasibility of a new standardized protocol to guide tracheostomy decannulation. Study Design Descriptive review of quality improvement project. Methods A quality improvement project was conducted in the inpatient setting of a tertiary urban academic hospital. Adult patients who had received a tracheostomy and for whom the indication for tracheostomy had resolved were included. A multidisciplinary task force reviewed input from clinicians caring for tracheostomy patients and developed a protocol for screening, capping, and decannulation. The primary outcome measured was successful decannulation. Results Fifty‐seven patients were screened for a capping trial over a 12‐month period; 54 were capped. Six patients were lost to follow‐up. Fifty patients passed the capping trial, and all 50 were decannulated successfully. When decannulation was pursued in one patient who had twice failed the screening criteria and subsequent capping trials, the patient failed decannulation and ultimately required reintubation for the management of secretions. The screening tool had high sensitivity (90%) and positive predictive value (100%) for successful decannulation. Additionally, the number of reported patient safety concerns decreased from seven in the 6 months preceding implementation of the program to one report in the 6 months after implementation. Conclusion The new tracheostomy capping and decannulation protocol assisted in predicting both successful and failed decannulation. Although several patients failed certain capping criteria initially, the protocol stipulated modifications of care that enabled successful decannulation. The screening tool had high sensitivity and promoted communication, standardization of practice, and patient safety. Level of Evidence 2b. Laryngoscope, 124:1794–1800, 2014